Land market distortions and aggregate agricultural productivity: Evidence from Guatemala - Britos, Braulio; Hernandez, Manuel A.; Robles, Miguel; Trupkin, Danilo R. (Elsevier, 2022)
Farm size and land allocation are important factors in explaining lagging agricultural productivity in developing countries. This paper examines the effect of land market imperfections on land allocation across farmers and aggregate agricultural productivity. We develop a theoretical framework to model the optimal size distribution of farms and assess to what extent market imperfections can explain non-optimal land allocation and output inefficiency. We measure these distortions for the case of Guatemala using agricultural census microdata. We find that due to land market imperfections aggregate output is 19% below its efficient level for both maize and beans and 31% below for coffee, which are three major crops produced nationwide. We also observe that areas with higher distortions show higher land price dispersion and less active rental markets. The degree of land market distortions across areas co-variate to some extent with road accessibility, ethnicity, and education.